Various Biological Activities of Pyridazinone Ring Derivatives - S. Banerjee, Pooja (Asian Journal of Chemistry, 2011)
In the recent years there has been an increasing interest in the chemistry of pyridazinone derivatives because of their biological significance. Pyridazinones have been reported to possess variety of biological activities like antidiabetic, anticancer, anti-AIDS, cardiovascular activity, antiinflammatory activity, anticonvulsant activity and potentially usable cerebroprotective agent. This paper summarizes the previous work on the various biological activities such as cardiovascular properties, antiinflammatory properties, analgesic properties, nociceptive properties, antidepressant properties, anticonvulsant properties, antidiabetic properties, antiasthmatic properties, anti-HIV1 properties, antiproliferative properties, antimicrobial properties, insecticidal properties of the pyridazine ring and pyridazinone derivatives.